How do digital transformation and green policies affect FDI flows in the ASEAN region? - Thao, Cao Phuong; Dat, Duong Quoc; Ha, Vu Thu; Oanh, Ngo Thi Tu; Quan, Dinh Anh (Journal of Empirical Studies, 2025)
In the era of digital transformation and sustainable development, both digitalization and environmental policies are increasingly central to national development strategies, especially in ASEAN. These transitions are reshaping investment environments and influencing the flow of Foreign Direct Investment (FDI). This study investigates the impact of digital transformation, green policies, and selected macroeconomic factors on FDI inflows in ASEAN countries. Using a balanced panel dataset covering six ASEAN economies from 2008 to 2022, the research applies the Fixed Effects Model (FEM) with robust standard errors to address heteroskedasticity and autocorrelation. Data were collected from six ASEAN countries from 2008 to 2022. Empirical findings show that higher Internet penetration significantly increases FDI inflows, while greater CO2 emission intensity tends to reduce investment attraction. Financial development also promotes FDI, confirming the role of an efficient financial system. Inflation exhibits mixed effects, reflecting diverse macroeconomic conditions among countries. Overall, the findings emphasize that both digital readiness and environmental commitment play vital roles in attracting sustainable and high-quality FDI, providing useful implications for ASEAN governments in fostering digital and green transformation to strengthen long-term investment competitiveness.